2005
DOI: 10.1111/j.1742-4658.2005.04976.x
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of the amyloid precursor protein‐like protein APLP2 by disintegrin‐metalloproteinases

Abstract: The amyloid precursor protein (APP) is a member of a protein family in mammals that includes the APP-like proteins APLP1 and APLP2 [1]. All APP ⁄ APLP family members are type I integral membrane proteins with large extracellular ectodomains and short cytoplasmic tails. Compared with APP, both APLPs are highly homologous in their amino acid sequence (e.g. APLP2 ⁄ APP 52% identical, 71% similar) [2] and are proteolytically processed in a similar way. The N-terminal ectodomains are released by a shedding enzyme [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 53 publications
(84 reference statements)
6
68
0
Order By: Relevance
“…2E, lanes 3 and 6). An increase in full-length TMEFF2 in cell lysates was not apparent by Western blot analysis (not shown), which is in good agreement with published data with other proteins such as the amyloid precursor protein-like protein (APLP2) (51). This reflects that only cell surface protein is cleaved from the cell membrane, representing a fraction of the total protein.…”
Section: Generation Of C-terminal Tmeff2 Fragments Is Affected By Botsupporting
confidence: 91%
“…2E, lanes 3 and 6). An increase in full-length TMEFF2 in cell lysates was not apparent by Western blot analysis (not shown), which is in good agreement with published data with other proteins such as the amyloid precursor protein-like protein (APLP2) (51). This reflects that only cell surface protein is cleaved from the cell membrane, representing a fraction of the total protein.…”
Section: Generation Of C-terminal Tmeff2 Fragments Is Affected By Botsupporting
confidence: 91%
“…26,27 APP, which is a type I transmembrane protein as well as APLPs, is cleaved consecutively, first at the extracellular juxtamembrane region by a-or b-secretase and secondly at the intramembrane region by g-secretase. 26 Similarly with APP, the N-terminal ectodomain of APLP2 is shedded by b-secretase 28,29 as well as by ADAM 10 and 17, 30 whereas the C-termini remain in the membrane 10,28 and can be further processed by g-or e-secretases 13,14 to release ICDs with signaling properties. 10,28 The APLP2-ICDs are known to interact with Fe65 via a YENPTY domain, which APP, APLP1 and APLP2 have in common in their C-terminus, translocating into the nucleus by Fe65-dependent manner 8 and show Fe65-dependent gene transcriptional activity by heterologous reporter genes.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, p3/ Ab-like fragments (Eggert et al 2004;Minogue et al 2009), as well as APLP1 and APLP2 intracellular fragments (termed ALIDs) are generated in a g-secretase dependent manner (Scheinfeld et al 2002;Walsh et al 2003). Whereas there has been robust evidence indicating that APLP2 is processed by a-and b-secretase (Eggert et al 2004;Pastorino et al 2004;Endres et al 2005), APLP1 shedding appeared to be independent of BACE activity as it was not affected by BACE inhibitors (Eggert et al 2004;Minogue et al 2009). A recent study using BACE-KO and overexpressing mice showed, however, that BACE deficiency substantially reduces brain APLP1s levels and that ICDs of APP family members are released in the absence of BACE (Frigerio et al 2010).…”
Section: App Gene Family and Structurementioning
confidence: 99%